Thoughts on the Need for Capacity Building for implementing Food and Nutrition Security Programs with Special Reference to Information, Communication Technologies - Thompson, Lorraine (Technical Centre for Agricultural and Rural Cooperation, 2005)
Presentation on theme 3: Information and Communication Tools in Food and Nutrition Security